THE METACOGNITIVE SELF-REGULATION OF STUDENTS TOWARD ENGLISH LEARNING ACHIEVEMENT AT X1 SMPN 2 DUAMPANUA PINRANG - Purnama, Suci; Asriati, Sitti; Hamid, Sitti Maryam (FKIP Unismuh Makassar, 2025)
This study used a quantitative approach. Quantitative research is research that in the process uses a lot of numbers starting from data collection, data interpretation, and display of results. The samples in this study were 58 students of SMP Negeri 2 Duampanua who were sitting in class IX. The formulation of the problem in this study is